Perancangan Proyek Resto & Bar dengan Pendalaman Efisiensi dan Konservasi Energi oleh Konsultan Arsitektur Filostudio - Dwitasari, Sebei Erfiera Beneditta; Indrawan, Stephanus Evert (Universitas Ciputra Surabaya, 2024)
Currently, one of the main issues in Indonesia is the issue of climate change due to large CO2 gas emissions in power plants. The Indonesia Economic Prospects report discusses how Indonesia can push climate commitments in the electricity sector into concrete action. Because of this, the government aims to reduce greenhouse gas emissions by 26 to 41 percent by 2030. The information for the study was gathered and assessed from newspapers and journals, in addition to using quantitative methods to collect data via questionnaires. In this research, it becomes increasingly important to design bars and restaurants, emphasizing energy efficiency and conservation to meet the current environmental and financial difficulties. This research aims to create a restaurant and bar project that promotes sustainable and efficient energy consumption and aesthetic and service considerations. Implement effective energy use by conducting site analysis of the surrounding environment using tools and software. The results of this analysis are used as basic data in efforts to implement energy efficiency that utilizes natural ventilation and lighting in restaurant and bar buildings without reducing thermal comfort. Apart from this application, energy use in buildings is also calculated with the help of software to obtain concrete results on the successful implementation of energy efficiency and conservation.